Assessment of capillary phenomena in liquid composite molding. (May 2019) - Caglar, Baris; Tekin, Cem; Karasu, Feyza; Michaud, Véronique
Abstract: The interplay between capillary and viscous forces plays a significant role for optimal part quality in fiber-reinforced composites manufactured by Liquid Composite Molding (LCM); these are however difficult to analyze during flow. Two approaches are proposed in this study: (i) a woven glass fabric's surface was modified by corona treatment to improve its wetting characteristics without altering its permeability, (ii) flow of a UV-curable resin was stopped during LCM by fast radiation cure. Capillary rise experiments and unsaturated/saturated permeability measurements confirmed the wetting improvement by corona treatment. Flow front morphology analysis of cured pristine and treated fabrics, processed under various pressure differentials, revealed the enhancement of dual-scale flow at capillary-dominated regime and improvement of intra-tow flow in viscous-dominated regime. Furthermore, the obtained results provide insight into the so-called optimal capillary number to attain the minimal void content in composites and its alteration by surface treatment of fiber reinforcements.